2005
DOI: 10.1002/adma.200500777
|View full text |Cite
|
Sign up to set email alerts
|

Photoembossing of Periodic Relief Structures Using Polymerization‐ Induced Diffusion: A Combinatorial Study

Abstract: Photoembossing is a solvent‐free photolithographic technique for the production of polymeric relief microstructures (see Figure). A combinatorial methodology to explore the influence of different parameters (e.g., processing temperature, binder content, photoinitiator content) on the resultant relief structure is presented using an acrylate‐based model system. Results are discussed in the framework of a diffusion‐polymerization model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 14 publications
4
89
0
Order By: Relevance
“…However, the majority of these methods involve photoablation, 21-26 photopolymerization [27][28][29] or photocrosslinking. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Hence, reversible SRG formation has not been reported in these systems.…”
Section: Introductionmentioning
confidence: 96%
“…However, the majority of these methods involve photoablation, 21-26 photopolymerization [27][28][29] or photocrosslinking. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Hence, reversible SRG formation has not been reported in these systems.…”
Section: Introductionmentioning
confidence: 96%
“…Much to our surprise, the increase of the height of the structures and their aspect ratio is much larger than what can be achieved by simply reducing the polymerization rate by the reduction of light intensity or initiator concentration alone. 14 This means that there must be an additional mechanism explaining the enormous effects of TBHQ, which we will try to elucidate in the following paragraphs.…”
mentioning
confidence: 99%
“…[1] Recently, it has been reported that colorless large SR structures due to mass transfer can be fabricated using materials that do not contain azobenzene compounds. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] It is considered that SR formation is concerned with photoreactioninduced internal diffusion processes. Recently, we have reported that the SR structure is fabricated by spatially patterned ultra-violet (UV) light, even in a general-purpose polystyrene (PS) film.…”
Section: Introductionmentioning
confidence: 99%